(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2015)
Risk management is especially challenging for risks, which cannot be modelled using historical data due to rapid technological, environmental or social changes in an increasingly complex, interconnected world. This article describes and illustrates the Top Risk Assessments and Scenario Analysis approaches which can be used to complement traditional risk modelling in these instances.